-(k-8)-7=-11+5k

Simple and best practice solution for -(k-8)-7=-11+5k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(k-8)-7=-11+5k equation:


Simplifying
-1(k + -8) + -7 = -11 + 5k

Reorder the terms:
-1(-8 + k) + -7 = -11 + 5k
(-8 * -1 + k * -1) + -7 = -11 + 5k
(8 + -1k) + -7 = -11 + 5k

Reorder the terms:
8 + -7 + -1k = -11 + 5k

Combine like terms: 8 + -7 = 1
1 + -1k = -11 + 5k

Solving
1 + -1k = -11 + 5k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-5k' to each side of the equation.
1 + -1k + -5k = -11 + 5k + -5k

Combine like terms: -1k + -5k = -6k
1 + -6k = -11 + 5k + -5k

Combine like terms: 5k + -5k = 0
1 + -6k = -11 + 0
1 + -6k = -11

Add '-1' to each side of the equation.
1 + -1 + -6k = -11 + -1

Combine like terms: 1 + -1 = 0
0 + -6k = -11 + -1
-6k = -11 + -1

Combine like terms: -11 + -1 = -12
-6k = -12

Divide each side by '-6'.
k = 2

Simplifying
k = 2

See similar equations:

| 124/6+44=h | | (4+w)(5w+6)=0 | | 7a+11=3a+21 | | 4c^3+4c^2-80c=0 | | 7x+22=9(x-4) | | 56/11 | | 2(5n+8)=-16+6n | | x+3=6(8-3x)-7 | | 7150=6.25*r*5 | | A=1/2*bh | | 5x+3y=40 | | -6a+28=-(2a-8) | | 9x^2+18x+17=0 | | 5c^3+30c-35c=0 | | 3(-8n-2)=-2n+16 | | 24x-4x^2=0 | | 3y-9=6y+3 | | 5x+5(2+6x)=10+3x | | (6+y)(3y+7)=0 | | (2x)lnx+x=0 | | -15-5r=5(1+3r) | | (5v-7)(3-v)=0 | | 4x+4=5x+10 | | (2n-3)(n+4)=0 | | 6c-6-2c-5-3c+7= | | 8+(x+5)= | | x^3-10x^2+13x+74=0 | | 5b+3(3b+4)=-24+2b | | x*2-x=20 | | v=(50-2x)(50-2x)(x) | | y=5*cos*2x+11 | | (5z+6)(4-z)=0 |

Equations solver categories